Artificial Cultivation of Ganoderma lucidum - Tiwari, C. K.; Meshram, P. B.; Patra, A. K. (Indian Forester, 2004)
Ganoderma lucidum is used in different hosts viz. Albizia lebbek , Boswellia serrata , Delonix regia , Populus deltoides , Leucaena leucocephala and Lannea coromandelica for artifical cultivation in control condition. The better performance was observed in Delonix regia for the production of G.lucidum.